Do sex hormones at birth predict later-life economic preferences? Evidence from a pregnancy birth cohort study. Issue 1941 (23rd December 2020) - van Leeuwen, Boris; Smeets, Paul; Bovet, Jeanne; Nave, Gideon; Stieglitz, Jonathan; Whitehouse, Andrew
Abstract : Economic preferences may be shaped by exposure to sex hormones around birth. Prior studies of economic preferences and numerous other phenotypic characteristics use digit ratios (2D : 4D), a purported proxy for prenatal testosterone exposure, whose validity has recently been questioned. We use direct measures of neonatal sex hormones (testosterone and oestrogen), measured from umbilical cord blood ( n = 200) to investigate their association with later-life economic preferences (risk preferences, competitiveness, time preferences and social preferences) in an Australian cohort (Raine Study Gen2). We find no significant associations between testosterone at birth and preferences, except for competitiveness, where the effect runs opposite to the expected direction. Point estimates are between 0.05–0.09 percentage points (pp) and 0.003–0.14 s.d. We similarly find no significant associations between 2D : 4D and preferences ( n = 533, point estimates 0.003–0.02 pp and 0.001–0.06 s.d.). Our sample size allows detecting effects larger than 0.11 pp or 0.22 s.d. for testosterone at birth, and 0.07 pp or 0.14 s.d. for 2D : 4D ( α = 0.05 and power = 0.90). Equivalence tests show that most effects are unlikely to be larger than these bounds. Our results suggest a reinterpretation of prior findings relating 2D : 4D to economic preferences, and highlight the importance of future large-sample studies that permit detection of small effects.